Interação in vitro entre espermatozoides de catetos (Pecari tajacu Linnaeus, 1758) e substratos heterólogos - Campos, Lívia Batista (2015)
Conventional tests that evaluate sperm quality do not have the ability to measure the potential of a fertilizing sample. This study aimed to determine the ability of the collared peccary of sperm in interacting with swine oocytes recovered from antral follicles, perivitelline membrane binding capacity of the chicken egg, and finally identify relationships between sperm parameters and in vitro interaction tests. Thus study was divided in two experiments with 11 male collared peccaries from the Multiplication Center of Wild Animals (CEMAS/UFERSA). In all experiments, the semen was collected by electroejaculation and evaluated for motility, vigour, viability, normal morphology, membrane integrity, and kinetic motility parameters by CASA. In the first experiment, semen samples were analyzed by an in vitro interaction test with swine oocytes conducted under a humidified atmosphere containing 5% CO2 for 18 h at 38.5ºC. Thus, it was found that in all oocytes there interactions with the presence of spermatozoa (mean 100.00 ± 0.0), observed the mean of 19.85 ± 5.5 oocytes penetrated by spermatozoa, number bound spermatozoa 39.4 ± 4.6 and penetrated spermatozoa 2.46 ± 0.7. Also, verified a significant association between the number of bound sperm and straightness (STR) (R2=61.7%; P=0.04). In the second experiment, semen samples were frozen in a Tris-based extender plus egg yolk (10%), Aloe vera (10%) and glycerol (6%). After thawing, samples were analyzed by an egg perivitelline membrane biding test conducted under a humidified atmosphere containing 5% CO2 for 20 min at 38.5ºC. As result, we identify 140.6 ± 19.4 sperm bound to the perivitelline membrane to fresh samples (binding range 33.9 308,7), while in frozen-thawed samples, a total of 125.1 ± 5.5 sperm were found (binding range 49.8 250.7) (P>0.05). Significant associations between frozen/thawed sperm bound to perivitelline membrane and various sperm parameters as vigor (54.6%), amplitude lateral head (R=55.1%), beat cross frequency (R=76.8%), straightness (R=61.8%) and linearity (R=62.2%) were found. In conclusion, that the two tests can be used for the functional evaluation of peccaries sperm. The perivitelline membrane binding test is a reliable, practical and relatively simple method that does not require expensive equipment and can be efficiently incorporated into the routine analysis of peccaries semen samples